Determinantes del abandono de cultivos de pitahaya en el cantón Palora, Morona Santiago - Vásquez Villalta, Elvis Fabricio (2025)
This study analyzes the determinants that influence the abandonment of pitahaya crops in the Palora canton, Morona Santiago province. In Palora, pitahaya cultivation represents a strategic activity for the cantonal economy; however, in recent years, there has been an increase in the abandonment of plantations, generating economic, social, and environmental impacts. To identify these determinants, a survey consisting of 21 open-ended and closed-ended questions was used, divided into two sections: a general section about the farmer and their socioeconomic and logistical situation; and a second section contextualizing the pitahaya production process. This survey was conducted among 343 farmers, of whom 46% still maintain pitahaya crops and 54% have abandoned them. The purpose was to characterize their socioeconomic situation, analyze the production process, and evaluate the factors that influence the permanence or abandonment of the crop. The data are analyzed using logit and probit models, selecting the probit model as the best due to its higher Pseudo R2, lower information loss (AIC/BIC), and higher maximum likelihood value. The results obtained in the probit model show that the age and educational level of the farmer have a direct relationship with abandonment at 13.93% and 2.68% respectively, while the variables that act inversely on abandonment are family size (5.62%), agricultural income (5.18%), non-agricultural income (9.84%), access to credit (7.55%), and farm size (3.36%).